Caribbean Growth in an International Perspective : The Role of Tourism and Size - Thacker, Nita.; Acevedo Mejia, Sebastian; Perrelli, Roberto (Washington, D.C. : International Monetary Fund, 2012)
After earlier success, growth performance in most Caribbean countries has been disappointing since the early 1990s. With slower growth, output has fallen behind that of relevant comparator countries. This paper analyzes the growth experience of the Caribbean countries from a cross country perspective. Three findings stand out. First, the slowdown in growth is explained more by a decline in productivity rather than a lack of investment. Second, tourism has been a significant contributor to higher growth (through both capital accumulation and productivity) and lower output volatility, and in many countries there is scope for further expansion of this sector. Third, the small size and the fact that most of these countries are islands have limited growth. Policies aimed at improving productivity, further development of the tourism sector, and regional integration could pay dividends in terms of higher growth in the region.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet